Techno-economic sensitivity analysis for optimization of carbon dioxide capture process by potassium carbonate solution. (1st September 2022) - Chuenphan, Thapanat; Yurata, Tarabordin; Sema, Teerawat; Chalermsinsuwan, Benjapon
Abstract: In this study, a potassium carbonate (K2 CO3 ) solution-based carbon dioxide (CO2 ) absorption process was efficiently improved and optimized by Aspen Plus. Sensitivity analysis with a 2 k factorial design was conducted to analyze both main and interaction effects of process parameters on CO2 removal efficiency and reboiler specific heat duty. It was found that the liquid-to-gas (L/G) mass ratio and CO2 concentration in sour gas were the two most important parameters affecting both responses. Additionally, a pilot-scale CO2 capture process was simulated for both K2 CO3 and monoethanolamine (MEA) solutions and compared in terms of CO2 removal efficiency, reboiler specific heat duty, and annual CO2 capture cost. The results showed that the optimal case for a K2 CO3 solution achieved 87.04% CO2 removal efficiency, reboiler specific heat duty of 2.17 GJ/T CO2, annual CO2 capture cost of 57.50 USD/T CO2, and exergy efficiency of 40.71%, while the MEA solution case showed 73.35% CO2 removal efficiency, 4.78 GJ/T CO2, annual CO2 capture of 107.50 USD/T CO2, and an exergy efficiency of 18.49%. Highlights: K2 CO3- based CO2 absorption process was efficiently optimized by Aspen Plus. L/G mass ratio and CO2 concentration were two important parameters in this process. Pilot CO2 capture process was compared in terms of techno-economics evaluation. Optimized specific reboiler duty was lower than conventional amine-based solutions. K2 CO3 solution possessed a promising feasibility in techno-economic aspects.